Acute bilateral vestibulopathy with simultaneous involvement of both superior and inferior vestibular nerves. Issue 5 (October 2020) - Ichijo, Kentaro; Kinoshita, Makoto; Fujimoto, Chisato; Uranaka, Tsukasa; Kikkawa, Yayoi S.; Sugasawa, Keiko; Yamasoba, Tatsuya; Iwasaki, Shinichi
Abstract: We report a case of acute vestibulopathy with the simultaneous involvement of both superior and inferior vestibular nerves on both sides. A 36-year-old female presented with dizziness, oscillopsia and a walking impairment subsequent to a high fever. Vestibular function tests including caloric testing, video head impulse testing (vHIT) and cervical and ocular vestibular evoked myogenic potentials (cVEMPs and oVEMPs) were performed. In the first examination, vHIT and caloric testing showed severe impairments in all three semicircular canals in each ear, and both cVEMPs and oVEMPs were absent on both sides. During a 1-year follow-up, the gain of vHIT gradually recovered by more than 0.5 to normal. cVEMPs also recovered to normal on both sides while oVEMPs remained absent on both sides. This is the first reported case of acute bilateral vestibulopathy with simultaneous involvement of both superior and inferior vestibular nerves on both sides. Repeated evaluation of vestibular function using vHIT, cVEMPs and oVEMPs is helpful to assess the time course of recovery in patients with vestibulopathy.